Wear Resistance and Failure Mode of Coatings Based on the ZrN System with the Introduction of Ti, Nb, and Hf Deposited on a Titanium Alloy Substrate - Sergey Grigoriev; Catherine Sotova; Alexander Metel; Valery Zhylinski; Filipp Milovich; Anton Seleznev; Yanpeng Xue; Alexey Vereschaka (Metals)
The article presents the results of a comparison of the wear resistance of coatings with a two-layer architecture (adhesion layer–wear-resistant layer) of Zr-ZrN, Zr-(Zr,Ti)N, Zr,Hf-(Zr,Hf)N, Zr,Nb-(Zr,Nb)N, Zr,Hf-(Ti,Zr,Hf)N, and Zr,Nb-(Ti,Zr,Nb)N coatings, deposited on a titanium alloy substrate. The wear resistance was studied using two different counterbodies: Al2O3 and steel. When in contact with the Al2O3 counterbodies, the best wear resistance was demonstrated by samples with Zr,Hf-(Zr,Hf)N and Zr,Nb-(Zr,Nb,Ti)N coatings. In tests conducted in contact with the steel counterbody, the best resistance was demonstrated by samples with Zr-ZrN and Zr,Hf-(Ti,Zr,Hf)N coatings. The wear resistance of samples with (Zr,Hf)N and (Zr,Nb,Ti)N coatings was 2.5–3.3 times higher than that of the uncoated sample. The Zr,Nb adhesion layer ensures better adhesion of the coating to the substrate. It was found that not only the adhesion strength of the adhesion layer to the substrate and coating is of significant importance but also the strength of the adhesion layer itself. The surface film of titanium oxide must be completely etched off to ensure maximum strength of the adhesive bond between the coating and the substrate. It has been established that the adhesion of the coating and the titanium substrate is also affected by the characteristics of the outer (wear-resistant) coating layer, which is the composition and structure of the wear-resistant coating layer. Delamination can occur both at the boundary of the adhesive layer with the substrate and at the boundary of the wear-resistant and adhesive layers of the coating depending on the strength of the adhesive bonds in the corresponding pair. It is necessary to ensure a good combination of properties both in the substrate–adhesion layer system and in the adhesion layer–wear-resistant layer system.